Proteome analysis of Duck Tembusu virus (DTMUV)‐infected BHK‐21 cells. Issue 12 (20th June 2017) - Sun, Xin; Wang, Shengyu; Lin, Xian; Zhao, Lianzhong; Zhang, Dan; Yi, Chenyang; Sun, Xiaomei; Chen, Huanchun; Jin, Meilin
Abstract : Duck Tembusu virus (DTMUV) is a newly emerging pathogenic flavivirus that has caused huge economic losses to the duck industry in China since 2010. Moreover, the infection has spread rapidly, posing a potential public health concern. In this study, iTRAQ approach was first used to quantitatively identify differentially expressed cellular proteins in DTMUV‐infected BHK‐21 cells which are usually employed to produce veterinary vaccines for DTMUV, as well as other flaviviruses by serial passage. We identified 192 differentially expressed cellular proteins, including 11 upregulated and eight downregulated proteins at 24 h postinfection (hpi), as well as 25 upregulated and 151 downregulated proteins at 48 hpi, of which TLR9, DDX3X, and DDX5 may play important roles in virus propagation. Further, DDX3X could inhibit DTMUV replication by modulating the IFN pathway via TBK1. In conclusion, our study is the first to analyze the protein profile of DTMUV‐infected cells by quantitative proteomics. We believe that our findings provide valuable information in better understanding the host response to DTMUV infection. These findings are particularly important in the development of vaccine‐based strategies.